Puberty Knowledge and Communication among Adolescent Sexual Offenders in Indonesia: A Qualitative Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2022)
Introduction: Rape against women, as one of sexual assaults now has been became a serius issue throughout the world in social and public health. It is a gross violation of women’s human rights, which can not be accepted from any perspectives. In the latest cases, the perpetrators of rape are conducted by adolescent or minor. These often occur and develop massively in many countries without any serious recovery on the victims. As a result, the rape assault has a profound impact on the victim personally and socially as well. Purpose: This article presents the study of the young sexual offenders’ knowledge on puberty and their sexual communication. Method: This research was qualitative toward 28 sexual perpetrators, all informants are undergoing sentences in Correctional Institutions of Bengkulu province, Indonesia. The informants were all child convicts, (aged less than 18 years) at four correctional institutions in Bengkulu province. All informants were male and aged between 16-18 years. Data was collected through semi-structured interviews with informants based on interview guidelines. Results of the study: The perpetrators of sexual assault were middle adolescents who were in-between 16 to 18 years. Based on the results of analysis, it was found that there were ineffective sexual communication patterns among perpetrators, both informants, communication parents, friends, teachers and couples. Moreover, this study found inadequate puberty knowledge among sexual offenders. Research limitations: This article only describes sexual communication and knowledge on puberty, while other individual factors and social aspects are not discussed at all in this article. Originality: Based on the various results of previous studies, there are no researches have been found that specifically examines the behavior of sexual violence by minors in Bengkulu province.
Keywords: Adolescent; Communication; Knowledge; Puberty; Sex offenders